(3GdCQHYhf Yf GdCQHYjf aj aVGFd CejQ GdeDefjfs - (3GdNRGYj GdfjSGHhQj, CHh SYjO, eMeO Hf CMeO Hf GdMSjf Hf CMeO, J b (B5 (3g`s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3HSe Gddg (B.. (3MOKfj GdTjN Gdabjg GdYGde TLGY GdOjf CHh YHO Gddg eMeO Hf CHj CMeO Hf eMeO Hf GdYjGT GdHjgbj (B... (3GedGkA HeOjfI eQGZI aj KGdK YTQ ef TgQ UaQ ef TghQ SfI CQHY hKdGKjf hNeSeGFIs
(3BNQgG (B:s
... (3ef MaX Ydi GeJj CQHYjf MOjKG ef GdSfI cfJ dg TajYG jhe GdbjGeI hdG Tc Cf aVGFd Ydj Hf CHj WGdH Ydjg GdSdGe ef GdSfIs
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj , heUMMI Ydi fSNI HNW (B: (3eMeO Ydj Hf MGL bGSe GdGSJQGHGPj GdehLhOI HGdfLa aj ecJHI GdTjN eMeO Ydj GdfLa BHGOj GdCUagGfjs
(3JHUQI GdYfhGf (B:s
(3aj aVGFd CejQ GdeDefjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\60s
(3GdPQjYI (B1 - 265 (2201)s
Keywords: (3GdMOjK hGdeUWdMs